2013
DOI: 10.1007/s00216-013-6876-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot-based lateral flow immunoassay for detection of chloramphenicol in milk

Abstract: A novel rapid (20 min) fluorescent lateral flow test for chloramphenicol (CAP) detection in milk was developed. The chosen format is a binding-inhibition assay. Water-soluble quantum dots with an emission peak at 625 nm were applied as a label. Milk samples were diluted by 20 % with phosphate buffer to eliminate the matrix effect. The result of the assay could be seen by eye under UV light excitation or registered by a portable power-dependent photometer. The limit of CAP detection by the second approach is 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(100 citation statements)
references
References 2 publications
0
100
0
Order By: Relevance
“…As noticed by Berlina, et al [24], the absence of detergent in the running solution does not allow the complete migration of QDs along the nitrocellulose membrane, so we tried the addition of different percentages (2.5, 5 and 10 %) of Tween 20 and Triton X-100. For our assay, we observed that Triton X-100 assured better QDs migration and provided a complete absence of nitrocellulose coloration outside the Test and Control lines (data not shown).…”
Section: Optimization Of Experimental Parametersmentioning
confidence: 99%
“…As noticed by Berlina, et al [24], the absence of detergent in the running solution does not allow the complete migration of QDs along the nitrocellulose membrane, so we tried the addition of different percentages (2.5, 5 and 10 %) of Tween 20 and Triton X-100. For our assay, we observed that Triton X-100 assured better QDs migration and provided a complete absence of nitrocellulose coloration outside the Test and Control lines (data not shown).…”
Section: Optimization Of Experimental Parametersmentioning
confidence: 99%
“…To overcome this limitation, researchers have worked on different labeling tags, including silver or gold enhancement (Anfossi et al, 2013;Hu et al, 2013), chemiluminescent tags or fluorescent tags (Zou et al, 2010;Berlina et al, 2013;Bruno, 2014;Taranova et al, 2015), magnetic nanoparticles Wang et al, 2013), and carbon nanoparticles (Noguera et al, 2011). Anfossi et al (2013) amplified the detection signal of an ochratoxin by using a detection LFTS that utilizes silver nucleation on gold nanoparticles.…”
Section: Labeling Tagsmentioning
confidence: 99%
“…Fluorescent nanoparticles or quantum dots (QDs) have high quantum yield and brightness, photostability, and resistance to chemical degradation. Several groups have reported QD-based LFTSs for food safety diagnosis including Listeria monocytogenes (Bruno, 2014), pesticide metabolites (Zou et al, 2010), antibiotics (Taranova et al, 2015), and chloramphenicol (Berlina et al, 2013). Taranova et al (2015) demonstrated qualitative and quantitative analysis capability of the LFTSs by using different-color emission QDs.…”
Section: Labeling Tagsmentioning
confidence: 99%
“…The above limitations of conventional LFIA have motivated the development of other labels instead of gold nanoparticles, including color latex, 14 magnetic nanoparticles 15 and various fluorescent reporters. 16,17 Especially, fluorescent reporters, such as time-resolved fluorescent nanoparticles, 17 upconverting phosphor 18,19 and quantum dots (QDs), 16,20,21 have attracted more attention due to the sensitivity, quantitative results and potential for multiplexing.…”
Section: Introductionmentioning
confidence: 99%
“…QDs-based LFIAs are frequently reported in recent literature and are used for detection of tumor markers, 24 toxins 16,25 and virus. 26 Mostly, the quantitative measurements were achieved by a specific commercial 21 or home-made 20,24 fluorescent strip reader.…”
Section: Introductionmentioning
confidence: 99%